Expectant management of missed miscarriage - Andi Asri, Andi Anggeriana; Mat Adenan, Noor Azmi; Esfehani, Ali Jafarzadeh; Mohtaruddin, Nurhafizah; Ma, Saung Oo; Abdul Latiff, Latiffah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
Early pregnancy losses occur in 10-20% of all pregnancies. Surgical evacuation has always been the mainstay of management of miscarriages. The main aim of this study was to understand the success rate of expectant management of miscarriage with regards to gestational sac size and period of gestation. The secondary outcome was to measure the satisfaction level and the rate of pregnancy after 6 month of expectant management. Patients diagnosed with missed miscarriages were requested to choose between expectant or surgical management. Those decided for expectant management on “wait and watch” approach were assessed weekly up to 5 completed weeks until complete miscarriage was achieved spontaneously. Surgical evacuation was performed if medically indicated or requested by the patients at any time or at the end of fifth week if complete miscarriage was not achieved. Out of 212 cases, 75 (35.4%) opted for expectant management. Complete miscarriage was achieved in 85.3% of subjects by the end of fifth weeks respectively. Mean of Gestational sac size and period of gestation was not found to influence the success rate of complete spontaneous miscarriage in the expectant management. No morbidity was recorded during the five weeks of the study period. Mean satisfaction score was 9.7±8.3. Pregnancy occurred in 47% of patients within 6 months follow up. The Receiver operation characteristic (ROC) curve analysis suggested the end of second week as the cut off for surgical intervention. This study revealed that expectant management of missed miscarriage is a reliable management of missed miscarriage within the first two weeks.